Fungal volatile organic compounds (FVOCs) contribution in olive oil aroma and volatile biogenesis during olive preprocessing storage. Issue 4 (5th April 2017) - Gharbi, Ines; Issaoui, Manel; Haddadi, Dorsaf; Gheith, Soukaina; Rhim, Amel; Cheraief, Imed; Nour, Mohamed; Flamini, Guido; Hammami, Mohamed
Abstract: The present paper reports on the impact of the microbial growth changes, occuring during fifteen days of cv . Chemlali preprocessing storage in different containers representing the common practice during olive processing (plastic bags, reticular bags, and plastic boxes), on olive oil quality. Next, the microorganisms of their microflora (Fungi) were isolated and identified and their effect on olive oil aroma and volatile biogenesis was evaluated by comparing the olive oil volatile profile versus fungal volatile organic compounds. HS‐SPME technique was used for volatile component sampling. Virgin olive oil (VOO) chemical quality indices did not show major variations during storage. Olive oil contained novel volatile compounds that could enhance its flavor, but also contained some off‐flavor compounds which could reduce its organoleptic characteristics and thus its quality. Results show that olive microflora can contribute to the biogenesis of olive oil volatiles and thus some genera could potentially be used to enhance olive oil aroma. Practical applications: The present paper try to assess the potential contribution of fungi in the biogenesis of volatiles found in olive oil. The identification of microorganisms capable of producing volatile compounds would have a great impact; the diverse functions of Fungal volatile organic compounds (FVOCs) can be developed for use in potential biotechnological applications (biofuel, biocontrol, etc.) with greater market value. For olive oil industry applications, some fungal volatile organic compounds are useful for the control of postharvest plant disease; someothers should be explored due to their antioxidant properties. Application of some of the microflora members or even application of enzymes that these microorganisms produce and that contribute to volatile biogenesis could have much to offer in olive oil quality.